Total synthesis of pseudouridine via Heck-type C-glycosylation12. (22nd May 2019) - Yu, Cheng-Ping; Chang, Hsin-Yun; Chien, Tun-Cheng
Abstract : Pseudouridine (1 ) was synthesized by functional group interconversions of the Heck adduct11 from 2, 4-dimethoxy-5-iodopyrimidine (8 ) and ribofuranoid glycal4 . Abstract : The reaction of 2, 4-dimethoxy-5-iodopyrimidine (8 ) and 3, 5-di- O-tert -butyldimethylsilyl protected ribofuranoid glycal4 was carried out with Pd(OAc)2 as the catalyst, PPh3 as the ligand and Et3 N as the base in DMF at 70 °C followed by desilylation to afford exclusively the β-anomer of 5-(2, 3-dideoxy-3-oxoribofuranosyl)-2, 4-dimethoxypyrimidine (11 ) in a very good yield. The subsequent protecting group and functional group interconversions furnished pseudouridine (Ψ, 1 ).